PIC MICROCONTROLLER AND EMBEDDED SYSTEMS b Using Assembly and C for PIC18 c Muhammad Ali Mazidi, Rolin D. McKinlay, Danny Causey - Mazidi, Muhammad Ali; McKinlay, Rolin D.; Causey, Danny E (MicroDigitalEd, 2016)
The PIC microcontroller from Microchip is one of the most widely used 8-bit microcontrollers in the world. In this book, the authors use a step-by-step and systematic approach to show the programming of the PIC18 chip. Examples in both Assembly language and C show how to program many of the PIC18 features such as timers, serial communication, ADC, and SPI.